Effect on genital warts in Australian female and heterosexual male individuals after introduction of the national human papillomavirus gender-neutral vaccination programme: an analysis of national sentinel surveillance data from 2004–18. Issue 12 (December 2021) - Chow, Eric P F; Carter, Allison; Vickers, Tobias; Fairley, Christopher K; McNulty, Anna; Guy, Rebecca J; Regan, David G; Grulich, Andrew E; Callander, Denton; Khawar, Laila; Machalek, Dorothy A; Donovan, Basil
Summary: Background: In Australia, the government-funded human papillomavirus (HPV) vaccination programme was introduced in April, 2007, for girls and young women, and in February, 2013, for boys. As of Dec 31, 2018, all Australian-born female individuals younger than 38 years and male individuals younger than 21 years have been eligible for the free quadrivalent or nonavalent HPV vaccine. We aimed to examine the trends in genital wart diagnoses among Australian-born female and heterosexual male individuals who attended sexual health clinics throughout Australia before and after the introduction of the gender-neutral HPV vaccination programme in February, 2013. Methods: We did a serial cross-sectional analysis of genital wart diagnoses among Australian-born female and heterosexual male individuals attending a national surveillance network of 35 clinics between Jan 1, 2004, and Dec 31, 2018. We calculated prevalence ratios of genital warts, using log-binomial regression models, for the female-only vaccination period (July 1, 2007, to Feb 28, 2013), gender-neutral vaccination period (March 1, 2013, to Dec 31, 2018), and the whole vaccination period (July 1, 2007, to Dec 31, 2018) compared with the pre-vaccination period (Jan 1, 2004, to June 30, 2007). Findings: We included 121 038 men and 116 341 women in the analysis. Overall, we observed a 58% reduction (prevalence ratio 0·42, 95% CI 0·40–0·44) in genital wart diagnoses in female individuals and a 45% reduction (0·55, 0·53–0·57) in genital wart diagnoses in heterosexual male individuals after the introduction of the vaccination programme in 2007. The largest reduction in genital warts was observed in younger individuals, and there was a decreasing magnitude of reduction with increasing age (80%, 72%, 61%, 41%, and 16% reductions in female individuals aged 15–20 years, 21–25 years, 26–30 years, 31–35 years, and ≥36 years, respectively; 70%, 61%, 49%, 37%, and 29% reductions in male individuals aged 15–20 years, 21–25 years, 26–30 years, 31–35 years, and ≥36 years, respectively). Significant reductions observed in female individuals (0·32, 0·28–0·36) and male individuals (0·51, 0·43–0·61) aged 15–20 years in the female-only vaccination period were followed by a more substantial reduction in female individuals (0·07, 0·06–0·09) and male individuals (0·11, 0·08–0·15) aged 15–20 years in the gender-neutral vaccination period. Interpretation: The national gender-neutral HPV vaccination programme has led to substantial and ongoing reduction in genital warts among Australian female and heterosexual male individuals, with a marked reduction in young individuals who received the vaccine at school. Funding: Seqirus Australia and the Australian Government Department of Health.